(untitled) (Quinto Sol, 2011)
This article discusses the various pros and cons of replacing salaried workforce by slaves in large livestock production units of the Río de la Plata at the end of the XVIIIth century and the beginnings of the 19th Century. It tries to show that, beyond its convenience at costs level, to form a big group of slaves was an investment of some risk, and represented a significant financial effort. In addition, it involved a rearrangement of organizational production patterns, which were not necessarily simple.